PENINGKATAN KEMAMPUAN GURU PADA EVALUASI PEMBELAJARAN MELALUI BIMBINGAN KELOMPOK DI SEKOLAH DASAR - Syukur . (Institut Pendidikan Tapanuli Selatan, 2021)
The lack of the teacher's ability to evaluate learning according to the K13 curriculum can be seen. From 8 teachers only 3 people (37.5%) can say that the ability in evaluating learning is quite good, while 5 people (62.5%) teachers have a low learning evaluation ability. . The purpose of this school action research is to increase the ability of teachers to evaluate learning through group guidance at SDN 163 / IX Karang Mulyo Kab. Muaro Jambi. This type of research is a school action research (PTS) in two cycles. The cycle consists of four stages, namely: planning, implementing, observing, reflecting. The target of this research is 5 class teachers. The data obtained are quantitative and qualitative data with data collection methods using observation sheets and field notes documentation then analyzed by percentage and data reduction. Based on the results of the research and discussion that has been described, it can be concluded that through group guidance it can increase the professional competence of teachers in evaluating learning in the K13 curriculum at SDN 163 / IX Karang Mulyo.